How Does the Spatial Confinement of FtsZ to a Membrane Surface Affect Its Polymerization Properties and Function? - Vélez, Marisela (Frontiers in Microbiology, 2022)
FtsZ is the cytoskeletal protein that organizes the formation of the septal ring and orchestrates bacterial cell division. Its association to the membrane is essential for its function. In this mini-review I will address the question of how this association can interfere with the structure and dynamic properties of the filaments and argue that its dynamics could also remodel the underlying lipid membrane through its activity, providing a new element, lipid rearrangement, to be considered when trying to understand how FtsZ activity serves to orchestrate all the proteins participating in the localized and concerted function of septal ring assembly and the synthesis of the peptidoglycan layer needed for bacterial division.